Self-Activating, Capacitive Anion Intercalation Enables High-Power Graphite Cathodes - Wang, Gang; Yu, Minghao; Wang, Jungang; Li, Debao; Tan, Deming; Loeffler, Markus; Zhuang, Xiaodong; Muellen, Klaus; Feng, Xinliang (Advanced Materials, 2018)
Developing high-power cathodes is crucial to construct next-generation quick-charge batteries for electric transportation and grid applications. However, this mainly relies on nanoengineering strategies at the expense of low scalability and high battery cost. Another option is provided herein to build high-power cathodes by exploiting inexpensive bulk graphite as the active electrode material, where anion intercalation is involved. With the assistance of a strong alginate binder, the disintegration problem of graphite cathodes due to the large volume variation of >130% is well suppressed, making it possible to investigate the intrinsic electrochemical behavior and to elucidate the charge storage kinetics of graphite cathodes. Ultrahigh power capability up to 42.9 kW kg−1 at the energy density of >300 Wh kg−1 (based on graphite mass) and long cycling life over 10 000 cycles are achieved, much higher than those of conventional cathode materials for Li-ion batteries. A self-activating and capacitive anion intercalation into graphite is discovered for the first time, making graphite a new intrinsic intercalation-pseudocapacitance cathode material. The finding highlights the kinetical difference of anion intercalation (as cathode) from cation intercalation (as anode) into graphitic carbon materials, and new high-power energy storage devices will be inspired.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Al-ion batteries; anion intercalation; dual-ion batteries; graphite cathodes; intercalation pseudocapacitance